A review of health resource tracking in developing countries. - Powell-Jackson, T; Mills, A (2007)
Timely, reliable and complete information on financial resources in the health sector is critical for sound policy making and planning, particularly in developing countries where resources are both scarce and unpredictable. Health resource tracking has a long history and has seen renewed interest more recently as pressure has mounted to improve accountability for the attainment of the health Millennium Development Goals. We review the methods used to track health resources and recent experiences of their application, with a view to identifying the major challenges that must be overcome if data availability and reliability are to improve. At the country level, there have been important advances in the refinement of the National Health Accounts (NHA) methodology, which is now regarded as the international standard. Significant efforts have also been put into the development of methods to track disease-specific expenditures. However, NHA as a framework can do little to address the underlying problem of weak government public expenditure management and information systems that provide much of the raw data. The experience of institutionalizing NHA suggests progress has been uneven and there is a potential for stand-alone disease accounts to make the situation worse by undermining capacity and confusing technicians. Global level tracking of donor assistance to health relies to a large extent on the OECD's Creditor Reporting System. Despite improvements in its coverage and reliability, the demand for estimates of aid to control of specific diseases is resulting in multiple, uncoordinated data requests to donor agencies, placing additional workload on the providers of information. The emergence of budget support aid modalities poses a methodological challenge to health resource tracking, as such support is difficult to attribute to any particular sector or health programme. Attention should focus on improving underlying financial and information systems at the country level, which will facilitate more reliable and timely reporting of NHA estimates. Effective implementation of a framework to make donors more accountable to recipient countries and the international community will improve the availability of financial data on their activities.